Electrically controllable magnetic properties of Fe-doped GaSe monolayer. (20th February 2019) - Ke, Congming; Wu, Yaping; Guo, Guang-Yu; Wu, Zhiming; Kang, Junyong
Abstract: Electrically controllable magnetic properties in 2D materials are promising for the development of the next-generation of magnetic and spintronic applications. In this paper, a theoretical design of magnetic property modulation in an Fe-doped GaSe monolayer is provided based on systematical density functional theory calculations. A ferromagnetic coupling between Fe and the vicinal Ga atom in the Fe-doped GaSe monolayer is found to be regulated to an antiferromagnetic coupling at a critical electric field of 0.2 V Å −1, accompanied with the change of the magnetic moment and the spin polarization. By calculating the magnetization energy, total energy, charge redistribution, and orbital-decomposed densities of states, the significant effect of the electric field on the magnetic configuration and magnetic anisotropy in the Fe-doped GaSe monolayer is analyzed, and the related physics mechanism is revealed. The electric-field tunable magnetic properties offer a promising application in magnetic and spintronic devices.